Differentiating the adhesion properties of surface proteins between various Borrelia species - Danklmaier, Anna-Celine (Jihočeská univerzita, 2022)
The aim of the thesis was to gain a better understanding of decorin binding proteins A and B (DbpAB) of various Borrelia species my different means. Overexpression of DbpA or DbpB in B. afzelii was addressed, examining phenotypic changes in mutants. Also, it was aimed to create shuttle vectors to complement DbpAB of different European Borrelia species as well as suicide vectors.
Differentiating the adhesion properties of surface proteins between various Borrelia species
Keywords: Borrelia; surface proteins; adhesion